Ochrobactrum anthropi: An emerging pathogen causing meningitis with sepsis in a neurotrauma patient: Meningitis and sepsis by O. anthropi - Rastogi, Neha; Mathur, Purva (The Journal of Infection in Developing Countries, 2017)
Ochrobactrum anthropi is an unusual emerging pathogen especially in the hospital environment. Most of the reported cases are nosocomially acquired infections in patients with various indwelling and invasive medical devices, such as central venous catheters and drainage tubes. We report a case of nosocomially transmitted invasive catheter related septicaemia with meningitis due to O. anthropi, in an elderly immunocompetent male with a head trauma admitted to a level -1 trauma centre. This report describes clinical and microbiological characteristics of rare pathogen and also highlights the importance of rapid identification, susceptibility testing of such opportunistic pathogens in trauma settings and its unique antibiotic susceptibility profiles. This requires prompt treatment with timely intervention, and appropriate antimicrobial therapy, alongside adherence to strict infection control practices.